2022
DOI: 10.26599/sab.2022.9060026
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in low-level laser therapy on depression

Abstract: Photobiomodulation (PBM), as a form of light therapy, has been applied broadly in the medical practice. The biological photoreceptors use small-molecule cofactors called chromophores to detect light and convert a physical signal into a biochemical signal transmission cascade. Visible light (380-780 nm) can activate specialized photoreceptors to stimulate vision and regulate circadian rhythm. Compared with visible light, near-infrared (NIR) light (780-1,100 nm) has better tissue penetration depths, enabling us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 131 publications
0
2
0
Order By: Relevance
“…It was found that 3LT improves the healing of soft tissues, reduces inflammation, and relieves chronic and acute physical and mental pain [73][74][75][76][77][78][79][80].…”
Section: Physical Characteristics Of Low Power/cold Laser Toolmentioning
confidence: 99%
“…It was found that 3LT improves the healing of soft tissues, reduces inflammation, and relieves chronic and acute physical and mental pain [73][74][75][76][77][78][79][80].…”
Section: Physical Characteristics Of Low Power/cold Laser Toolmentioning
confidence: 99%
“…Thus, it can reduce glutamate excitotoxicity and improve depression side effects and complications. 61 We can take advantage of the unique low-energy light to execute the non-invasive combination approach or to boost favorable signaling pathways by engaging molecular signals. Deeper penetration is vital for the application of LLLT to reach deep brain tissues and activate preventive or regenerative processes, as well as preventing muscular atrophy in individuals who have lost their capacity to move normally.…”
Section: Low-level Light Therapy In Depressionmentioning
confidence: 99%